The Artificial Intelligence (AI) and the Future of Political Communication: Artificial Intelligence (AI) and the Future of Political Communication - Sripech, Yongwit; Bhukrongna, Watanyu (RATANABUTH JOURNAL, 2023)
This article aims to highlight the importance of artificial intelligence (AI) becoming a significant part of political communication through the rapid advancement of technology. It is impossible to overlook the potential of technology in revolutionizing political activism, public opinion analysis, and public policy formulation. The birth of AI has evolved to incorporate new strategies and algorithms capable of processing massive amounts of data, allowing campaigns to target specific demographics with personalized messages. Analyzing user behavior on social media and online search patterns can help identify potential supporters and tailor campaign messages to align with their interests and values. These goal-oriented strategies expand the reach of political activism and connect with individual voters more effectively, ultimately influencing their decision-making processes by providing data-driven insights. However, the integration of AI in political communication raises ethical concerns, particularly related to privacy and data security. Thus, striking a balance between using AI for political communication and safeguarding individual privacy will be crucial in the future. While ethical considerations must be taken into account, the future of political communication is undoubtedly intertwined with AI. As AI continues to advance, its impact on political discourse and decision-making processes will only deepen.